Effects of psychological interventions on competitive anxiety and athletic performance in golfers: a systematic review and meta-analysis - Longhui Li; Zilong Zhao; Xuewen Li; Yang Yi (BMC Sports Science, Medicine and Rehabilitation, 2026)
Abstract Background Competitive anxiety is common in golf and can negatively affect athletic performance. Psychological interventions are widely used to manage competitive anxiety and enhance performance; however, evidence specific to golfers has not yet been systematically synthesized. This study aims to evaluate the effects of psychological interventions on competitive anxiety and athletic performance in golfers. In addition, subgroup analyses were conducted to explore potential sources of variation in intervention effects. Methods A systematic search of Cochrane, Embase, PubMed, Scopus, and Web of Science identified randomized and non-randomized controlled trials evaluating psychological interventions to reduce competitive anxiety or improve athletic performance in golfers. Risk of bias was assessed using the revised Cochrane risk-of-bias tool for randomized trials and the Risk Of Bias In Non-randomized Studies of Interventions tool. Certainty of evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation approach. Meta-analyses were performed using Stata 18.0. Results A total of 15 studies involving 606 participants were included. Nine studies were rated as low risk of bias, four as having some concerns, and two as moderate risk of bias. Psychological interventions were associated with reductions in competitive anxiety (SMD = − 0.29, 95% CI: −0.57 to − 0.02) and improvements in athletic performance (SMD = 0.70, 95% CI: 0.28 to 1.12). Substantial heterogeneity was observed for athletic performance outcomes (I² = 80.3%). Exploratory subgroup analyses suggested that effects may be more evident among male and amateur golfers and in studies using interventions delivered two to three times per week for sessions lasting up to 30 min. Conclusions Psychological interventions were associated with small reductions in competitive anxiety and moderate improvements in athletic performance in golfers. However, the certainty of the evidence was low, and substantial heterogeneity, limited evidence for subgroup analyses, and potential publication bias should be considered when interpreting the findings. Future research should prioritize high-quality randomized controlled trials with more balanced representation across gender and competitive level, and further examine specific dimensions of competitive anxiety as well as emerging approaches such as mindfulness-based interventions and technology-assisted methods including virtual reality and biofeedback. Trial registration PROSPERO: CRD420251025181.